Web Based Tea Powder Sales Information System at Juma Sidamanik Tea Shop - Luaha, Lius; Burhanuddin Damanik; Kristina Sitorus (CV. AFDIFAL MAJU BERKAH, 2025)
The background of this research is that the sales system is still manual which takes a long time in creating sales reports, is prone to recording errors, stock information and business competition in the dynamics of information technology development, so it is necessary to implement a web-based sales information system. The object of the research is Toko Teh Juma, a trading business engaged in the sale of black tea and green tea. Currently, Juma Tea still uses manual systems such as recording sales, stock items, and monthly reports. The solution offered is the creation of a sales information system that can make recording more effective. This system was developed using the Python language and uses SQLite as a database. This system is made web-based which must be connected to the internet. The system development method used in this research is the waterfall method . In this method, application development will go through several separate stages so that it is hoped that everything that is done is easy to design, analyze, and also easy to provide feedback. The results of this website-based information system research can help admins to calculate stock items and carry out daily or monthly reports. The conclusion of this research is that a web-based sales information system has been designed and built using a web front end and back end , SQLite is used to create a database, and has been tested with black box testing to view stock items and sales reports more easily. A web-based tea powder sales information system makes it easier for admins to create sales reports at the Juma Sidamanik Tea shop.